Finding a Relative Testing approach for Service Oriented Architecture (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
A SOA (Service Oriented Architecture) is an enterprise-scale IT architecture for linking resources on demand. In a SOA, resources are made available to participants in a value net, enterprise, and line of business. Service-oriented applications can be expensive to test because services are hosted remotely, are potentially shared among many users, and may have costs associated with their invocation. For interactive web services development SOA is a good approach. To find the desire outcomes from this architecture, we have to test this architecture than we can develop desire services from this architecture. There lots of works has done to test this architecture, like unit and integration testing are used to test this architecture but these methods cannot give hundred present testing capacity. In this paper we are concentrating to find a right approach to test the SOA. Regression testing is a better approach, rather than the previous methods.